Myocardial fibrosis and sudden cardiac death (SCD) risk factors in mitral valve prolapse patients deemed to be at low SCD risk - Doubell, J; Doubell, A; Steyn, J; Talle, M; Rajah, M; Herbst, P (SA Heart Journal, 2026)
Introduction: Mitral valve prolapse (MVP) is associated with risk for sudden cardiac death (SCD); however, there is no consensus regarding risk stratification. Myocardial fibrosis is a substrate for SCD in these patients. Risk markers described for SCD are T wave inversion in the inferior leads and complex ventricular ectopy (ventricular couplets, non-sustained ventricular tachycardia [NSVT], and polymorphic ventricular ectopy), spiked configuration of the lateral annular velocities (Pickelhaube sign), and mitral annular disjunction (MAD). Purpose: We aimed to investigate the prevalence of these risk factors in our population of MVP patients, a cohort clinically assessed as low risk for SCD. Furthermore, we aimed to investigate the association between these risk factors and myocardial fibrosis and to describe its pattern. Methods: Our echocardiography database was reviewed from 1 October 2020 to 31 December 2021 for patients with MVP. Patients newly diagnosed from 1 July 2021 to 31 March 2023 were also enrolled. Investigations included a clinical evaluation, assessment for SCD risk markers with electrocardiography (ECG), a 48-hour Holter ECG, a transthoracic echocardiogram, and an assessment for myocardial fibrosis with cardiovascular magnetic resonance (CMR) imaging. Results: A total of 39 patients, deemed to be at low SCD risk, without prior severe mitral regurgitation, malignant arrhythmias, cardiogenic syncope, or survived SCD, were included for analysis. Of the patients, 66% had areas of replacement fibrosis detected by late gadolinium enhancement (LGE). Segments commonly involved included the basal posterior (39%), basal inferior (39%), and basal lateral (25%). Areas involved were focal, with an average of 1.3 segments involved (± 1.3). No patient had diffuse fibrosis as assessed by extracellular volume (ECV) expansion. Known risk factors in our cohort included inferior T wave inversion (10%), polymorphic ventricular ectopy (18%), NSVT (16%), MAD (49%), and Pickelhaube sign (15%). No correlation was found between replacement fibrosis and any SCD risk marker. Conclusion: Replacement fibrosis and SCD risk markers were common in this cohort, which was considered low SCD risk. No association was found between fibrosis and risk markers, suggesting poor predictive power for fibrosis. Risk markers for SCD are described in preselected, high-risk MVP populations. The extent to which these risk markers reflect SCD risk in low-risk patients is unclear. Using these risk markers in clinically low-risk patients may over-assess the risk, potentially resulting in medicalising patients and inappropriate therapy.